Empirical Negation, Co-negation and Contraposition Rule I: Semantical Investigations - Niki, Satoru (Bulletin of the Section of Logic, 2020)
We investigate the relationship between M. De's empirical negation in Kripke and Beth Semantics. It turns out empirical negation, as well as co-negation, corresponds to different logics under different semantics. We then establish the relationship between logics related to these negations under unified syntax and semantics based on R. Sylvan's CCω.